PENGARUHÃÂ PRESTASIÃÂ BELAJARÃÂ DANÃÂ PRESTASIÃÂ PRAKTIKÃÂ PENGALAMANÃÂ LAPANGANÃÂ TERHADAPÃÂ MINATÃÂ MAHASISWAÃÂ MENJADIÃÂ GURUÃÂ ÃÂ - Yulirtanto, BibitÃƒÂ‚Ã‚Â ; ÃƒÂ‚Ã‚Â BurhanÃƒÂ‚Ã‚Â , M.; Hadromi, - (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Negeri Semarang, 2008)
TujuanÃÂ penelitianÃÂ iniÃÂ adalahÃÂ mengetahui:ÃÂ (1)ÃÂ prestasiÃÂ belajar,ÃÂ prestasiÃÂ PPLÃÂ danÃÂ minatÃÂ mahasiswaÃÂ menjadiÃÂ guru;ÃÂ (2)ÃÂ PengaruhÃÂ prestasiÃÂ belajarÃÂ danÃÂ PPLÃÂ terhadapÃÂ minatÃÂ mahasiswaÃÂ menjadiÃÂ guru;ÃÂ (3)ÃÂ PengaruhÃÂ prestasiÃÂ belajarÃÂ terhadapÃÂ minatÃÂ mahasiswaÃÂ menjadiÃÂ guru;ÃÂ danÃÂ (4)ÃÂ PengaruhÃÂ prestasiÃÂ PPLÃÂ terhadapÃÂ minatÃÂ mahasiswaÃÂ menjadiÃÂ guruÃÂ SMK.ÃÂ PopulasiÃÂ penelitianÃÂ adalahÃÂ 80ÃÂ orangÃÂ mahasiswaÃÂ PTMÃÂ 2005ÃÂ denganÃÂ jumlahÃÂ sampelÃÂ 45ÃÂ orang.ÃÂ PengambilanÃÂ sampelÃÂ menggunakanÃÂ teknikÃÂ randomÃÂ sampling.ÃÂ TeknikÃÂ pengumpulanÃÂ dataÃÂ menggunakanÃÂ dokumentasi,ÃÂ observasiÃÂ danÃÂ angket.ÃÂ TeknikÃÂ analisisÃÂ yangÃÂ digunakanÃÂ adalahÃÂ deskriptif,ÃÂ regresiÃÂ gandaÃÂ danÃÂ parsial.ÃÂ AnalisisÃÂ deskriptifÃÂ menunjukkanÃÂ bahwaÃÂ prestasiÃÂ belajar,ÃÂ prestasiÃÂ PPLÃÂ danÃÂ minatÃÂ menjadiÃÂ guruÃÂ SMKÃÂ mahasiswaÃÂ PendidikanÃÂ TeknikÃÂ MesinÃÂ UnnesÃÂ berturutÃ¢â¬ÂturutÃÂ memenuhiÃÂ kriteriaÃÂ sangatÃÂ memuaskan,ÃÂ sangatÃÂ tinggiÃÂ danÃÂ tinggi.ÃÂ AnalisisÃÂ regresiÃÂ gandaÃÂ menunjukkanÃÂ pengaruhÃÂ prestasiÃÂ belajarÃÂ danÃÂ prestasiÃÂ PPLÃÂ terhadapÃÂ minatÃÂ menjadiÃÂ guruÃÂ sebesarÃÂ 79,60%. ÃÂ KataÃÂ Kunci:ÃÂ PraktikÃÂ PengalamanÃÂ LapanganÃÂ (PPL),ÃÂ MinatÃÂ MenjadiÃÂ GuruÃÂ SMKÃÂ TheÃÂ aimsÃÂ ofÃÂ thisÃÂ researchÃÂ areÃÂ toÃÂ discover:ÃÂ (1)ÃÂ theÃÂ studyÃÂ achievement,ÃÂ fieldÃÂ experienceÃÂ practice,ÃÂ andÃÂ studentsÃ¢â¬â¢ÃÂ interestÃÂ toÃÂ beÃÂ teachers;ÃÂ (2)ÃÂ theÃÂ effectÃÂ ofÃÂ studyÃÂ achievementÃÂ andÃÂ fieldÃÂ experienceÃÂ practiceÃÂ towardÃÂ studentsÃ¢â¬â¢ÃÂ interestÃÂ toÃÂ beÃÂ teachers;ÃÂ (3)ÃÂ theÃÂ effectÃÂ ofÃÂ studyÃÂ achievementÃÂ towardÃÂ studentsÃ¢â¬â¢ÃÂ interestÃÂ toÃÂ beÃÂ teachers;ÃÂ (4)ÃÂ theÃÂ effectÃÂ ofÃÂ fieldÃÂ experienceÃÂ practiceÃÂ towardÃÂ studentsÃ¢â¬â¢ÃÂ interestÃÂ toÃÂ beÃÂ vocationalÃÂ highÃÂ schoolÃÂ teachers.ÃÂ TheÃÂ populationÃÂ ofÃÂ thisÃÂ researchÃÂ wasÃÂ 80ÃÂ studentsÃÂ ofÃÂ MechanicalÃÂ EngineeringÃÂ EducationÃÂ yearÃÂ 2005ÃÂ withÃÂ 45ÃÂ studentsÃÂ asÃÂ sample.ÃÂ TheÃÂ sampleÃÂ takingÃÂ usedÃÂ randomÃÂ samplingÃÂ technique.ÃÂ TheÃÂ dataÃÂ collectedÃÂ usedÃÂ documentation,ÃÂ observation,ÃÂ andÃÂ questionnaire.ÃÂ TheÃÂ analysisÃÂ techniquesÃÂ usedÃÂ wereÃÂ descriptive,ÃÂ doubleÃÂ regression,ÃÂ andÃÂ partialÃÂ technique.ÃÂ DescriptiveÃÂ analysisÃÂ showsÃÂ thatÃÂ theÃÂ studyÃÂ achievement,ÃÂ fieldÃÂ experienceÃÂ practice,ÃÂ andÃÂ MechanicalÃÂ EngineeringÃÂ EducationÃÂ studentsÃ¢â¬â¢ÃÂ interestÃÂ toÃÂ beÃÂ vocationalÃÂ highÃÂ schoolÃÂ teachersÃÂ successfullyÃÂ fulfillÃÂ veryÃÂ satisfactoryÃÂ criteria,ÃÂ veryÃÂ high,ÃÂ andÃÂ high.ÃÂ DoubleÃÂ regressionÃÂ analysisÃÂ showsÃÂ theÃÂ percentageÃÂ ofÃÂ theÃÂ effectÃÂ ofÃÂ studyÃÂ achievementÃÂ andÃÂ fieldÃÂ xperienceÃÂ practiceÃÂ achievementÃÂ towardÃÂ studentsÃ¢â¬â¢ÃÂ interestÃÂ toÃÂ beÃÂ teachersÃÂ isÃÂ 79,60%. ÃÂ Keywords:ÃÂ FieldÃÂ ExperienceÃÂ PracticeÃÂ (ppl),ÃÂ interestÃÂ toÃÂ beÃÂ vocationalÃÂ highÃÂ schoolÃÂ teachers ÃÂ